Memory, language, and bilingualism theoretical and applied approaches - Altarriba, Jeanette 1964-; Isurin, Ludmila (Cambridge, United Kingdom Cambridge University Press, 2013)
"The relationship between memory and language and the topic of bilingualism are important areas of research in both psychology and linguistics and are grounded in cognitive and linguistic paradigms, theories and experimentation. This volume provides an integrated theoretical/real-world approach to second language learning, use and processing from a cognitive perspective. A strong international and interdisciplinary team of contributors present the results of various explorations into bilingual language processing, from recent advances in studies on bilingual memory to studies on the role of the brain in language processing and language forgetting. This is a strong yet balanced combination of theoretical/overview contributions and accounts of novel, original, empirical studies which will educate readers on the relationship between theory, cognitive experimentation and data and their role in understanding language learning and practice"--Provided by publisher.
Machine generated contents note: Introduction Jeanette Altarriba and Ludmila Isurin; 1. Bilingual memory: structure, access, and processing James Bartolotti and Viorica Marian; 2. Lexical competition in localist and distributed connectionist models of L2 acquisition Ton Dijkstra, Femke Haga, Alex Bijsterveld and Ida Sprinkhuizen-Kuyper; 3. Working memory and (second) language processing Arnaud Szmalec, Marc Brysbaert and Wouter Duyck; 4. Working memory in simultaneous interpreters Teresa M. Signorelli and Loraine Obler; 5. Using electrophysiological measures to track the mapping of words to concepts in the bilingual brain: a focus on translation Janet G. van Hell and Judith F. Kroll; 6. Age effects in L2 learning: comparing child and adult learners' performance on tests of implicit and explicit memory Pavel Trofimovich, Sandra Martin-Chang and Kyle Levesque; 7. Bilingualism, language and aging Mira Goral; 8. Crossovers and codeswitching in the investigation of immigrant autobiographical memory Carmit Altman, Robert W. Schrauf and Joel Walters; 9. Linguistic relativity and bilingualism Panos Athanasopoulos and Fraibet Aveledo; 10. Testing effects for novel word learning in Chinese-English bilinguals Chi-Shing Tse and Xiaoping Pu; 11. The lexicon in second language attrition: what happens when the cat's got your tongue? Kathleen Bardovi-Harlig and David Stringer; 12. Memory and first language forgetting Ludmila Isurin; 13. Future research directions: bilingualism, memory, and language Jeanette Altarriba.
Includes bibliographical references and index.
Keywords: Bilingualism -- Psychological aspects; Cognition; Memory; Psycholinguistics